Implizite Derivation und Verbstammkonversion im Dänischen - Rajnik, Eugeniusz (Folia Scandinavica Posnaniensia, 2009)
The article reviews various definitions of implicit derivation and conversion as applied to Danish verbs turned into nouns. The nouns are divided into classes on the basis of their derivational history and their role in the system of the language. The conversion of verb stems, a productive word-formational type in contemporary Danish, is singled out for special treatment.